Antiviral high-strength decorative board and preparation method thereof
By applying the composite material with impregnation treatment on the high-strength fiber substrate board of the decorative plate, the problem that the decorative plate is prone to attach viruses and bacteria in the public environment is solved, long-term antibacterial and antiviral effects and excellent mechanical properties are achieved, production costs are reduced, and iron tailings resources are utilized.
Patent Information
- Application Number
- CN202211556359.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-06
AI Technical Summary
Existing decorative boards are prone to viruses and bacteria in public environments. Conventional disinfection methods have safety risks and poor durability. The production cost of wood substrates is high and the resources are scarce. The low content of iron tailings active ingredients leads to insufficient molding strength of the decorative board substrate layer.
A high-strength fiber substrate board is used as the substrate, combined with the decorative layer of the glue-impregnated treatment and the kraft paper layer, and nanotitanium dioxide, graphene and superhydrophobic nanoparticle composite materials are used to form a decorative board with antibacterial and antiviral effects.
It has achieved the long-term antibacterial and antiviral effects of decorative panels and excellent mechanical properties, reduced production costs, reduced the amount of gelling materials, realized the utilization of iron tailings resources, and is harmless to the human body, with significant social and economic benefits.
Smart Images

Figure CN115891381B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a decorative plate, in particular to an antiviral high-strength decorative plate and a preparation method thereof. Background Art
[0002] At present, the manufacture of decorative panels is mostly a composite finishing layer on the surface of a wooden substrate. The wooden substrate is relatively lacking in fire resistance, water resistance, corrosion resistance, environmental protection, safety and firmness, and resources are scarce, resulting in the continuous increase in the production cost of the wooden substrate, which is difficult to meet the needs of decoration. Iron tailings are mainly composed of siliceous and iron components, with a low impurity content, and are solid waste discharged by the steel industry. Large amounts of stockpiled iron tailings not only cause a waste of resources, but also lead to serious environmental and ecological pollution. At present, ordinary iron tailings are used to manufacture the substrate layer of decorative panels, which can play a role in fire prevention, water resistance, and corrosion resistance. However, due to the low content of active ingredients in ordinary iron tailings, it takes a long time to take effect. If it is directly used to prepare cement substrates, the binding force with the material is weak, and the structure is prone to looseness, which affects the molding strength of the substrate layer of the decorative panel, resulting in the decorative panel being easily deformed during construction and use, and the service life is not long.
[0003] In recent years, the infection rate of various respiratory diseases in humans has remained high. In particular, the new coronavirus that broke out in recent years has posed a great threat to human life and safety, and caused inestimable losses to the ecological environment and economy. In this context, public health safety has received more and more attention, and people's awareness of preventing viruses and bacteria has gradually increased. The decorative panels such as furniture panels, wall panels, and floors in gathering public environments such as hospitals, supermarkets, and schools are very easy to attach viruses and bacteria. The conventional method of eliminating viruses and bacteria attached to the decorative panel facing layer is to spray alcohol and 84 disinfectant, etc., but alcohol and disinfectant have a short retention time, poor sterilization and disinfection durability, and need to be used frequently. In addition, alcohol is flammable and disinfectant is highly irritating, which poses safety hazards and has a high risk factor. In addition, the existing decorative panel facing layer lacks antibacterial and antiviral capabilities or has unsatisfactory antibacterial and antiviral effects, resulting in viruses and bacteria in public areas being easily transmitted to the human body, seriously threatening human health and life safety.
[0004] Therefore, developing decorative panels with excellent mechanical properties and long-lasting and effective antibacterial and antiviral effects for long-term use in homes and public environments to protect human health has become the focus of research on decorative panels. Summary of the invention
[0005] The purpose of the present invention is to provide an antiviral high-strength decorative board and a preparation method thereof in view of the problems existing in the prior art. The antiviral high-strength decorative board of the present invention has the advantages of low cost, good dimensional stability, fire resistance, moisture resistance, corrosion resistance, high strength, impact resistance, antibacterial and antiviral, etc.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An antiviral high-strength decorative board, comprising a high-strength fiber substrate board, a decorative layer located above the high-strength fiber substrate board, and a kraft paper layer located above the decorative layer, wherein the decorative layer and the kraft paper layer are both treated with dipping, and the dipping solution used for the dipping treatment comprises the following components in weight percentage: 10-20% of aqueous polyurethane, 5-10% of nano-titanium dioxide, 1-5% of graphene, 10-20% of super-hydrophobic nanoparticles, and the balance of water; the preparation method of the dipping solution comprises: 1) mixing the nano-titanium dioxide, graphene, and super-hydrophobic nanoparticles at a rate of 300-350 r / min at 300-800° C. for 30-60 min, cooling, and nano-scale crushing to obtain a waterproof antiviral composite material; 2) adding the waterproof antiviral composite material and aqueous polyurethane into water and mixing them at high speed to obtain a dipping solution; the super-hydrophobic nanoparticles are silicon dioxide, and the particle size of the super-hydrophobic nanoparticles is 5-200 nm.
[0008] Dipping treatment method: Place the decorative paper or kraft paper in the dipping solution for dipping, dip it in the solution for 5 to 8 minutes at room temperature, then dry and cure it at 110 to 240°C for 1 to 15 minutes, so that the dipping solution adheres to the surface of the decorative paper or kraft paper.
[0009] The present invention performs a resin dipping treatment on the outer layer of the decorative board, that is, the decorative layer and the kraft paper layer, adds nano titanium dioxide and graphene into the resin dipping, and composites super-hydrophobic nanoparticles under high temperature conditions to form an antibacterial and antiviral material with super-hydrophobic properties. The antibacterial and antiviral material reacts with water or air under the action of light to generate active functional groups such as superoxide free radicals O2- and hydroxyl free radicals OH with high reactivity. These functional groups have extremely strong oxidizing ability and can quickly, effectively and almost non-selectively oxidize and decompose polluting organic matter (pathogenic bacteria, viruses, odor molecules, allergens, etc.) It can remove certain structures of molecules (such as corpses of mites and pollen), cut the molecular bonds of organic matter, decompose to produce non-toxic small molecules such as carbon dioxide and water, thereby effectively preventing viruses from entering host cells, causing the viruses to lose their living conditions and die. The hydrophobicity of the antibacterial and antiviral material can also make water contaminated by viruses or bacteria fall off and prevent it from adhering to the surface of the decorative board; the antibacterial and antiviral material with a ternary heterogeneous structure is formed by the composite of nano-titanium dioxide, graphene and super-hydrophobic nanoparticles, so that the components have a synergistic effect, which jointly improves the antibacterial and antiviral effect and mechanical properties of the decorative board.
[0010] Furthermore, the waterborne polyurethane is one of polyester waterborne polyurethane, polyether waterborne polyurethane and polycarbonate waterborne polyurethane.
[0011] Furthermore, in order to obtain antibacterial and durable high-strength decorative panels, the present invention discloses that the raw materials of the high-strength fiber substrate panel include 12-15% by weight of a first iron tailing, 15-30% by weight of a second iron tailing, 10-15% by weight of silicate cement, 2-8% by weight of modified fiber, 10-20% by weight of a calcium material, 3-5% by weight of an activator, 3-5% by weight of a water reducer, and the remainder being water; wherein the first iron tailing is obtained by ball-milling the iron tailing to a particle size of 80-200 um; the second iron tailing is obtained by calcining the iron tailing at a high temperature, rapidly cooling it, mixing it with an alkaline activator, and then ball-milling it to a particle size of <80 um; and the calcium material is one or more of hydroxyapatite, dicalcium phosphate, and calcium oxide.
[0012] Preferably, the alkaline activator is 10% by weight of the iron tailings raw material in the second iron tailings.
[0013] Preferably, the high temperature calcination temperature is 1100-1300°C.
[0014] Preferably, the modified fiber is prepared by soaking basalt fiber with a particle size of 10 to 30 mm in an alkaline solution at 40 to 80° C. for 3 to 8 hours and then mixing it with nanocellulose at a mass ratio of 2:1.
[0015] The present invention effectively improves the interaction between iron tailing molecules by combining calcination, rapid cooling and alkali soaking. The interface bonding force between the iron tailing and the modified fiber in the formula system is enhanced, and the flexural strength of the substrate board is improved in synergy with cement and calcium materials.
[0016] Furthermore, the preparation method of the high-strength fiber substrate board includes the following steps: after mixing the first iron tailings, the second iron tailings, silicate cement, fiber, and calcium material, adding an activator, a water reducer and water, stirring evenly at 60°C, cooling to room temperature, and using a molding pressure of 1.5 to 2.5 MPa to press-form a board; sending it into a steaming kettle and steaming it at 120 to 150°C for 4 to 6 hours to obtain a high-strength fiber substrate board, and cutting it according to construction needs and size requirements.
[0017] The present invention also discloses a method for preparing an antiviral high-strength decorative board, wherein the decorative layer and the kraft paper layer after the dipped glue treatment are sequentially pressed on the high-strength fiber substrate board by a hot press, and the pressing conditions are as follows: hot pressing for 40 minutes at a temperature of about 140 degrees and a pressure of 2.0-4.0 MPa; and cooling to obtain the decorative board.
[0018] Preferably, an inorganic ceramic coating layer is further provided between the high-strength fiber substrate plate and the decorative layer.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention solidifies the antibacterial and antiviral components in the decorative layer and the kraft paper layer through the dipping process, so that the decorative board has long-term antibacterial and antiviral effects and excellent mechanical properties. When the board is used in furniture, wall panels, countertops and other household and public indoor decoration places, there is no need to spray sterilization and disinfection water. It is environmentally friendly and healthy, and harmless to the human body, with significant social and economic benefits.
[0021] 2. The raw materials of the high-strength substrate board provided by the present invention are selected from iron tailings treated in different ways and mixed with cement, composite fiber, and calcium material to synergistically improve the mechanical properties of the substrate board, reduce the amount of cementitious materials, reduce production costs, and realize the resource utilization of industrial waste. No toxic or harmful gases and waste are generated in the entire production process, which is an environmentally friendly technology.
[0022] 3. The antiviral high-strength decorative board of the present invention has the advantages of low cost, fire resistance, moisture resistance, corrosion resistance, pollution resistance, wear resistance, high strength, impact resistance, antibacterial and antiviral, and good dimensional stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The following are the combustion performance test results of the decorative panels according to the embodiments of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The aqueous polyurethane used in the embodiment of the present invention is Wengkaier S339A, and the bulk density of the iron tailings is 2000-2200 kg / m 3 The strength of silicate cement is 42.5, the activator and alkaline activator are both sodium hydroxide, the nanocellulose is Shengquan nanocellulose FNFC-D993, the alkali solution is a saturated solution of sodium hydroxide, and the water reducer is a commercially available polycarboxylate water reducer with a water reduction rate of ≥25%. The super-hydrophobic nanoparticles are silicon dioxide, and the particle size of the super-hydrophobic nanoparticles is 5 to 200 nm.
[0026] A decorative panel hot pressing forming method:
[0027] 1) The decorative layer and the kraft paper layer after the resin treatment are sequentially pressed on the high-strength fiber substrate by a hot press, wherein the pressing conditions are: hot pressing for 40 minutes at a temperature of about 140 degrees and a pressure of 2.0-4.0 MPa, and the heating medium is steam, superheated water or hot oil;
[0028] The method for treating the decorative layer and the kraft paper layer with glue is as follows: the decorative paper or kraft paper is placed in a glue solution for dipping, the dipping is carried out at room temperature for 5 to 8 minutes, and then dried and cured at 110 to 240° C. for 1 to 15 minutes, so that the glue solution adheres to the surface of the decorative paper or kraft paper.
[0029] 3) The decorative board is obtained after cooling for 30 minutes, and the cooling medium is water;
[0030] 4) After the temperature drops to room temperature, the pressure is released, the board is unloaded from the machine, and the edges are sawed and the back is sanded to obtain the finished decorative board.
[0031] As an embodiment of the present invention, an inorganic ceramic coating layer may be provided between the high-strength fiber substrate plate and the decorative layer, which is more beautiful and durable.
[0032] Example 1
[0033] A high-strength fiber substrate board: 13% of a first iron tailing, 20% of a second iron tailing, 10% of silicate cement, 5% of modified fiber, and 10% of a calcareous material are mixed, 4% of an activator, 3% of a water reducer, and water are added, and stirred evenly at 60°C, and then cooled to room temperature and pressed into a plate at a molding pressure of 1.5 to 2.5 MPa; the plate is sent to a steaming kettle and steamed at 130°C for 5 hours to obtain a high-strength fiber substrate board.
[0034] Among them, the first iron tailings is obtained by ball-milling the iron tailings to a particle size of 80 to 200 um; the second iron tailings is obtained by calcining the iron tailings at high temperature, rapidly cooling the iron tailings, mixing with an alkaline activator, and then ball-milling to less than 80 um, the alkaline activator is 10% of the weight of the iron tailings raw material in the second iron tailings, and the calcination temperature is 1200°C; the calcitic material is one or more of hydroxyapatite, dicalcium phosphate, and calcium oxide.
[0035] The modified fiber is prepared by mixing basalt fiber with a particle size of 10 to 30 mm with nanocellulose at a mass ratio of 2:1 after being soaked in 50° C. alkali solution for 5 hours.
[0036] The high-strength fiber substrate board was tested according to the standard JC / T564.1-2008. The 28d air-dried flexural strength of the high-strength fiber substrate board of the present invention was 28.8MPa.
[0037] Comparative analysis of substrate board performance optimization:
[0038] Control experiment ①: substrate board, the difference from Example 1 is that the second iron tailings is iron tailings calcined at high temperature and then naturally cooled to room temperature, and then ball-milled to less than 80um after adding alkaline activator. The 28d air-dried flexural strength of the substrate board is 17.5MPa.
[0039] Control experiment ②: substrate board, different from Example 1, is the preparation of high-strength fiber substrate board: 13% of the first iron tailings, 20% of the second iron tailings, 10% of silicate cement, 5% of modified fiber, and 10% of calcium material are mixed, and then 4% of activator, 3% of water reducer and water are added and stirred at room temperature, and then the molding pressure is 1.5-2.5MPa to press the board; the board is sent to the steam curing kettle and steamed at 130℃ for 5h to obtain the substrate board. The 28d air-dried flexural strength of the substrate board is 19.6MPa after testing.
[0040] Control test ③: substrate board, the difference from Example 1 is that the modified fibers are all basalt fibers, and the modified fibers are prepared by soaking basalt fibers with a particle size of 10 to 30 mm in 50°C alkali solution for 5 hours. The 28d air-dried flexural strength of the substrate board was tested to be 20.9 MPa.
[0041] Example 2
[0042] A decorative board:
[0043] 1) Preparation of high-strength fiber substrate board: the same as in Example 1.
[0044] 2) Preparation of the impregnation solution: 1) Mixing 8% of the nano titanium dioxide, 3% of graphene, and 15% of super-hydrophobic nanoparticles at a rate of 300-350 r / min at 600° C. for 40 min, cooling and nano-scale crushing, sieving through 200 meshes, and obtaining a waterproof and antiviral composite material; 2) Adding the waterproof and antiviral composite material and 15% of aqueous polyurethane into water and mixing at high speed to obtain a impregnation solution.
[0045] 3) Decorative layer and kraft paper layer are treated with glue.
[0046] 4) The product is obtained by hot pressing.
[0047] Example 3
[0048] 1) High-strength fiber substrate board: The preparation method of the high-strength fiber substrate board comprises the following steps: 12% of the first iron tailings, 30% of the second iron tailings, 12% of silicate cement, 2% of modified fiber, and 20% of calcium material are mixed, 5% of activator, 3% of water reducer and water are added, and stirred evenly at 60°C, and then cooled to room temperature and pressed into a plate with a molding pressure of 1.5 to 2.5 MPa; the plate is sent to a steaming kettle and steamed at 150°C for 4 hours to obtain a high-strength fiber substrate board.
[0049] Among them, the first iron tailings is obtained by ball milling the iron tailings to a particle size of 80 to 200 um; the second iron tailings is obtained by calcining the iron tailings at high temperature, rapidly cooling the iron tailings, mixing with an alkaline activator, and then ball milling to less than 80 um, and the alkaline activator is 10% of the weight of the iron tailings raw material in the second iron tailings; the calcic material is one or more of hydroxyapatite, dicalcium phosphate, and calcium oxide.
[0050] The modified fiber is prepared by mixing basalt fiber with a particle size of 10 to 30 mm with nanocellulose at a mass ratio of 2:1 after being soaked in 80° C. alkali solution for 3 hours.
[0051] The 28d air-dried flexural strength of the substrate plate of the present invention is tested to be 27.9 MPa.
[0052] 2) Preparation of the impregnation solution: 1) Mixing 5% of the nano titanium dioxide, 5% of graphene, and 20% of super-hydrophobic nanoparticles at a rate of 300-350 r / min at 800° C. for 30 min, cooling and nano-scale crushing, sieving through 200 meshes to obtain a waterproof and antiviral composite material; 2) Adding the waterproof and antiviral composite material and 20% of water-based polyurethane into water and mixing at high speed to obtain a dipping solution.
[0053] 3) Decorative layer and kraft paper layer are treated with glue.
[0054] 4) The product is obtained by hot pressing.
[0055] Example 4
[0056] 1) High-strength fiber substrate board: The preparation method of the high-strength fiber substrate board comprises the following steps: 15% of the first iron tailings, 15% of the second iron tailings, 12% of silicate cement, 8% of modified fiber, and 10% of calcium material are mixed, 3% of activator, 5% of water reducer and water are added, and stirred evenly at 60°C, and then cooled to room temperature and pressed into a plate with a molding pressure of 1.5-2.5MPa; the plate is sent to a steaming kettle for steaming at 120-150°C for 4-6h to obtain a high-strength fiber substrate board.
[0057] Among them, the first iron tailings is obtained by ball milling the iron tailings to a particle size of 80 to 200 um; the second iron tailings is obtained by calcining the iron tailings at high temperature, rapidly cooling the iron tailings, mixing with an alkaline activator, and then ball milling to less than 80 um, and the alkaline activator is 10% of the weight of the iron tailings raw material in the second iron tailings; the calcic material is one or more of hydroxyapatite, dicalcium phosphate, and calcium oxide.
[0058] The modified fiber is prepared by mixing basalt fiber with a particle size of 10 to 30 mm with nanocellulose at a mass ratio of 2:1 after being soaked in 40° C. alkali solution for 8 hours.
[0059] The 28d air-dried flexural strength of the substrate plate of the present invention is tested to be 28.4 MPa.
[0060] 2) Preparation of the impregnation solution: 1) Mixing 10% of the nano titanium dioxide, 5% of graphene, and 10% of super-hydrophobic nanoparticles at a rate of 300-350 r / min at 300° C. for 60 min, cooling and nano-scale crushing, sieving through 200 meshes to obtain a waterproof and antiviral composite material; 2) Adding the waterproof and antiviral composite material and 10% of water-based polyurethane into water and mixing at high speed to obtain a dipping solution.
[0061] 3) Decorative layer and kraft paper layer are treated with glue.
[0062] 4) The product is obtained by hot pressing.
[0063] Comparative Example 1
[0064] A decorative board, which is different from Example 2 in that no super-hydrophobic nanoparticles are added to the waterproof and antiviral composite material, and the content of nano-titanium dioxide is 18.9% and the content of graphene is 7.1%.
[0065] Comparative Example 2
[0066] A decorative board, which is different from Example 2 in that the dipping solution is prepared as follows: 1) 8% of the nano titanium dioxide and 3% of graphene are mixed at a rate of 300-350 r / min at 600°C for 40 minutes, then cooled for nano-scale crushing, and sieved through 200 mesh to obtain a waterproof and antiviral composite material; 2) The waterproof and antiviral composite material, 15% super-hydrophobic nanoparticles, and 15% aqueous polyurethane are added to water and mixed at high speed to obtain a dipping solution.
[0067] Decorative board overall performance test:
[0068] Three decorative boards prepared in Examples 2 to 4 and Comparative Examples 1 to 2 were selected, each with a sample size of 600 mm × 600 mm × 6 mm, and their performance was tested according to the method of Q / ZC01-1.5-2021 "Asbestos-free fiber cement decorative board (high-density ice and fire board)". The specific test results are shown in Table 1 below.
[0069] Table 1 Technical indicators and performance test results of decorative panels
[0070]
[0071] 12 decorative board samples (specification 50×50 mm) of Example 2 and Comparative Examples 1-2 were selected, and the antibacterial properties of the decorative boards were tested according to JIS Z2801:2010 standard, with the standard value being: antibacterial activity value ≥ 2.0. As shown in Table 2.
[0072] Table 2 Antibacterial test
[0073]
[0074]
[0075] The test results show that the present invention fixes the waterproof and antiviral material on the surface of the decorative layer and the kraft paper layer by dipping in glue, so that the decorative board has a higher surface hardness and excellent wear resistance. This is due to the chemical bonding between the waterproof and antiviral materials, which forms a stable network interpenetrating structure between the three substances, thereby improving the surface hardness and wear resistance, and will not shrink or crack with changes in external temperature, thereby improving the antibacterial and antiviral properties of the decorative board. The finished decorative board has an antibacterial property of more than 99.9% against Escherichia coli and Staphylococcus aureus, is non-toxic, and has a long-lasting antibacterial and antiviral effect.
[0076] In addition, the present invention also conducted a combustion performance test on Example 2. The sample quantity was 5 pieces of 1500mm×1000mm×6mm, 5 pieces of 1500mm×500mm×6mm, 1 piece of 250mm×250mm×6mm, and 6 pieces of 400mm×20mm×6mm. The test results are shown in the attached Figure 1 After testing, the samples of the present invention all meet the requirements of Class A flat-plate building materials in standard GB8624-2012.
[0077] To sum up, the decorative panels produced using the technical solution of the present invention have excellent properties such as wear resistance, water resistance, corrosion resistance, pollution resistance, impact resistance, fire resistance, and good dimensional stability. They are easy to clean and have strong practicality. They can be widely used in home and public interior decoration places such as furniture, wall panels, and countertops. The width, length, and thickness of the antiviral high-strength decorative panels of the present invention can be made into different sizes as required. During production, they can be prefabricated in the factory and then assembled at the construction site, which is convenient for large-scale production and construction.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antiviral high-strength decorative board, characterized in that: The decorative board includes a high-strength fiber substrate board, a decorative layer located above the high-strength fiber substrate board, and a kraft paper layer located above the decorative layer. The decorative layer and the kraft paper layer are both treated with dipping, and the dipping solution used for the dipping treatment includes the following components in weight percentage: 10-20% aqueous polyurethane, 5-10% nano-titanium dioxide, 1-5% graphene, 10-20% super-hydrophobic nanoparticles, and the remainder water; the preparation method of the dipping solution: 1) mixing the nano-titanium dioxide, graphene, and super-hydrophobic nanoparticles at a rate of 300-350r / min at 300-800°C for 30-60min, cooling, and nano-scale crushing to obtain a waterproof and antiviral composite material; 2) adding the waterproof and antiviral composite material and aqueous polyurethane into water and mixing them at high speed to obtain a dipping solution; the super-hydrophobic nanoparticles are silicon dioxide, and the particle size of the super-hydrophobic nanoparticles is 5-200nm.
2. The antiviral high-strength decorative board according to claim 1, characterized in that: The raw materials of the high-strength fiber substrate plate include 12-15% by weight of a first iron tailing, 15-30% by weight of a second iron tailing, 10-15% by weight of silicate cement, 2-8% by weight of modified fiber, 10-20% by weight of a calcium material, 3-5% by weight of an activator, 3-5% by weight of a water reducer, and the remainder being water; wherein the first iron tailing is obtained by ball-milling the iron tailing to a particle size of 80-200 um; the second iron tailing is obtained by calcining the iron tailing at a high temperature, rapidly cooling it, mixing it with an alkaline activator, and then ball-milling it to a particle size of less than 80 um; the calcium material is one or more of hydroxyapatite, dicalcium phosphate, and calcium oxide.
3. The antiviral high-strength decorative board according to claim 2, characterized in that: The modified fiber is prepared by soaking basalt fiber with a particle size of 10 to 30 mm in alkali solution at 40 to 80° C. for 3 to 8 hours and then mixing it with nanocellulose at a mass ratio of 2:
1.
4. The antiviral high-strength decorative board according to claim 2, characterized in that: The preparation method of the high-strength fiber substrate board comprises the following steps: mixing the first iron tailings, the second iron tailings, silicate cement, modified fiber, and calcium material, adding an activator, a water reducer, and water, stirring evenly at 60° C., cooling to room temperature, and pressing and forming a board using a molding pressure of 1.5 to 2.5 MPa; sending the board into a steaming kettle and steaming at 120 to 150° C. for 4 to 6 hours to obtain a high-strength fiber substrate board.
5. The method for preparing an antiviral high-strength decorative board according to any one of claims 1 to 4, characterized in that: The decorative layer and the kraft paper layer after the resin impregnation treatment are sequentially pressed on the high-strength fiber substrate board by a hot press, and the pressing conditions are as follows: hot pressing at a temperature of 140° C. and a pressure of 2.0-4.0 MPa for 40 minutes; and cooling to obtain the decorative board.
6. The method for preparing an antiviral high-strength decorative board according to claim 5, characterized in that: An inorganic ceramic coating layer is also provided between the high-strength fiber substrate plate and the decorative layer.
Citation Information
Patent Citations
Graphene decorative plate and preparation method thereof
CN106812017A
Graphene glass fiber wall base cloth and its manufacturing method
CN107641977A